Role of Lipid Transfer Proteins (LTPs) in the Viral Life Cycle - Avula, Kiran; Singh, Bharati; Kumar, Preethy V.; Syed, Gulam H. (Frontiers in Microbiology, 2021)
Viruses are obligate parasites that depend on the host cell machinery for their replication and dissemination. Cellular lipids play a central role in multiple stages of the viral life cycle such as entry, replication, morphogenesis, and egress. Most viruses reorganize the host cell membranes for the establishment of viral replication complex. These specialized structures allow the segregation of replicating viral RNA from ribosomes and protect it from host nucleases. They also facilitate localized enrichment of cellular components required for viral replication and assembly. The specific composition of the lipid membrane governs its ability to form negative or positive curvature and possess a rigid or flexible form, which is crucial for membrane rearrangement and establishment of viral replication complexes. In this review, we highlight how different viruses manipulate host lipid transfer proteins and harness their functions to enrich different membrane compartments with specific lipids in order to facilitate multiple aspects of the viral life cycle.